An extension of a theorem of Sahab, Khan, and Sessa - A. R. Khan; N. Hussain (International Journal of Mathematics and Mathematical Sciences)
A fixed point theorem of Fisher and Sessa is generalized to locally convex spaces and the new result is applied to extend a recent theorem on invariant approximation of Sahab, Khan, and Sessa.